2021
DOI: 10.1177/2049936121991374
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and antibiotic resistance: a deadly combination

Abstract: Climate change is driven primarily by humanity’s use of fossil fuels and the resultant greenhouse gases from their combustion. The effects of climate change on human health are myriad and becomingly increasingly severe as the pace of climate change accelerates. One relatively underreported intersection between health and climate change is that of infections, particularly antibiotic-resistant infections. In this perspective review, the aspects of climate change that have already, will, and could possibly impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 57 publications
(70 reference statements)
0
64
0
Order By: Relevance
“…Temperature increased with the result of global warming is linked with the bacterial infections and their antibiotic resistance capabilities. Augmented temperature increases horizontal gene transfer, a crucial mechanism for the acquisition of antibiotic resistance (Burnham 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature increased with the result of global warming is linked with the bacterial infections and their antibiotic resistance capabilities. Augmented temperature increases horizontal gene transfer, a crucial mechanism for the acquisition of antibiotic resistance (Burnham 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also discussed the positive correlation between the incidence of bacterial infections with rising temperatures, humidity, and monthly precipitation [69]. A study of three clinically relevant pathogens (E. coli, K. pneumoniae and S. aureus) across Energies 2021, 14, 5938 7 of 13 41 states in the US confirmed that warmer temperatures can drive bacterial growth and also potentially drive resistance acquisition through horizontal gene transfer.…”
Section: Interrelationship Between Climate Change Covid-19 and Amrmentioning
confidence: 99%
“… 120–123 Other indirect effects of warming on antibiotic resistance have also been demonstrated. 119 Human bacterial infection rates have been correlated with increasing temperature for reasons probably related to increased pathogen burden in the environment, an increasing number of extreme weather events, as well as changing human behavior due to both short-term weather and long-term climate effects (Burnham). These factors all play a role in increased exposure to potential antibiotic resistant pathogens in the environment as well as in increased antibiotic prescribing.…”
Section: Antimicrobial Resistance and Climate Changementioning
confidence: 99%